2020
DOI: 10.1002/jor.24954
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus cell regional phenotypes: Dedifferentiation and reversal by biomaterial embedding

Abstract: Meniscus injuries are common and a major cause of long-term joint degeneration and disability. Current treatment options are limited, so novel regenerative therapies or tissue engineering strategies are urgently needed. The development of new therapies is hindered by a lack of knowledge regarding the cellular biology of the meniscus and a lack of well-established methods for studying meniscus cells in vitro.The goals of this study were to (1) establish baseline expression profiles and dedifferentiation pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Genes such as COL1A1, COL2A1, aggrecan (ACAN) and SOX9 are commonly used to determine the phenotype of meniscal cells however, it was recently reported that COL2A1 and ACAN may not be suitable markers for meniscal cells since they have significantly low expression levels in the meniscus. 22,23 Some studies have found a dramatic downregulation of COL2A1 mRNA, 24,25 while some was unable to detect the expression in cell culture, 26 including ours. It is important to note that some conditions such as injury, degeneration, cell culture environment and extracellular matrix component that is used during culturing may change gene expression profile.…”
Section: Discussionmentioning
confidence: 60%
“…Genes such as COL1A1, COL2A1, aggrecan (ACAN) and SOX9 are commonly used to determine the phenotype of meniscal cells however, it was recently reported that COL2A1 and ACAN may not be suitable markers for meniscal cells since they have significantly low expression levels in the meniscus. 22,23 Some studies have found a dramatic downregulation of COL2A1 mRNA, 24,25 while some was unable to detect the expression in cell culture, 26 including ours. It is important to note that some conditions such as injury, degeneration, cell culture environment and extracellular matrix component that is used during culturing may change gene expression profile.…”
Section: Discussionmentioning
confidence: 60%
“…For example, in FB1 and FB2 clusters, Col5a1 , Col12a1 , Col14a1 and Fndc1 were highly expressed, which are genes associated with fibrillogenesis and fibrillary homeostasis in connective tissues 26 – 29 . In the FB5 and FB6 clusters, Chad , Comp and Cilp appeared to be more active ECM markers, which are genes associated with chondrogenesis and injury repair in fibrocartilage 30 , 31 . Co22a1 is especially active in the FB4 cluster, suggesting potential functions related to myotendinous junctions and vascular stability in this cell population 32 34 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were isolated from the inner third and outer two-thirds of porcine medial menisci from skeletally mature female pigs obtained from a local abattoir, as previously described ( Riera et al, 2011 ; McNulty et al, 2013 ; Andress et al, 2021 ). Briefly, menisci were separated into inner and outer regions and minced.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, only a few studies have compared the responses of inner and outer zone cells to mechanical stimulation ( Furumatsu et al, 2012 ; Kanazawa et al, 2012 ). The meniscus inner and outer zones vary in regard to cellular phenotype ( Upton et al, 2006a ; Son and Levenston, 2012 ; Grogan et al, 2017 ; Andress et al, 2021 ), ECM composition, and mechanical properties ( Cheung, 1987 ; Scott et al, 1997 ; Sanchez-Adams et al, 2011 ), and experience different forces in vivo ( Upton et al, 2006b ; Freutel et al, 2014 ). Therefore, the inner and outer zone cells may exhibit differences in mechanoresponsiveness.…”
Section: Introductionmentioning
confidence: 99%